Accuracy of transfer of bite recording to simulated prosthetic reconstructions - Hellmann, Daniel; Etz, Eike; Giannakopoulos, Nikolaos Nikitas; Rammelsberg, Peter; Schmitter, Marc; Schindler, Hans J. (Clinical oral investigations, 2013)
A key aspect of complex restorative therapy is reconstruction of a new three-dimensional jaw relation. The objective of this study was to test the hypotheses that the initially recorded jaw relation would deviate substantially from the jaw position of the prosthetic reconstruction and that activity ratios of the jaw muscles would be significantly different for each of these jaw positions.
Gesehen am 09.04.2021
Published: 31 January 2012